Improvement of Leadership Competencies and Organizational Culture through Whole Brain Based-Interventions: A Case Study of Phoenix Thailand, Ltd. - Kokitsawat, Panpilai; Clapp, Ph.D., Ray (ABAC ODI JOURNAL Vision. Action. Outcome, 2015)
Abstract This action research aim to improve Leadership Competencies and Organizational Culture of the study group at leader and supervisors levels of Phoenix Ltd. through Whole Brain Based-Interventions, namely: Whole Brain Appreciative Coaching (WBAC), Appreciative Inquiry (AI), and Appreciative Leadership (AL). The Action Research was conducted using two dependent variables: Leadership Competencies and Organizational Culture; while three Whole Brain-Based Interventions comprised the Independent Variables. Both qualitative and quantitative data were used for assessment of both control and study group. The Competing Value Framework was utilized as the research instrument for both Organization Culture and Leadership Competencies. The Organization Culture Assessment Indicator (OCAI) describes four organizational structures: Clan, Adhocracy, Market and Hierarchy. The Managing Skill Assessment Indicator (MSAI) was used for Leadership competencies assessment including both transformational and transactional competencies. Managing teams, Interpersonal Relation, Development of others, Innovation, Future and Continuous Improvement were assessed as Transformational dimensions. Whereas, Managing Acculturation, Control System, Coordination, Competitiveness, Emerging employees and Customer Focus were assessed as Transactional dimension. For the study group the results showed a statistically significant change in four out of the six competencies that support Transformational Leadership. However, there was no significant change in the culture of either the study group or the control group. These results show that the three interventions in total provided a useful enhancement to the leadership competencies of the study group. Keywords: leadership competencies, organizational culture, Competing Values Framework, Whole Brain Appreciative Coaching, Appreciative Inquiry, Appreciative Leadership.